Tools for teacher assessment development - Yagües Cebrián, Álvaro (Avances en Supervisión Educativa, 2016)
Starting from the idea that the highest levels of success of an education system depend largely on the quality of teachers and considering that the current regulatory framework defines assessment as a valuable tool for monitoring and assessment of results and improvement of the processes, it is essential to establish the general characteristics of this assessment, evaluation procedures and tools and the strong involvement of inspectorate of education in a process that should be one of its priority duties and responsibilities.Considering the need to establish a framework in the form of rubric, we try to check in short the main procedures and instruments for carrying teacher assessment, analyzing their advantages and disadvantages, always from the perspective of inspectorate of education.
Keywords: quality of education; inspectorate of education; teacher assessment; tools for teacher assessment